Comparative Analysis of Educational Policies: A Cross-Country Study on Access and Equity in Primary Education - Asfahani Asfahani; Zohaib Hassan Sain; Mariana Mariana (EDUJAVARE: International Journal of Educational Research, 2023)
Access to quality primary education is a critical component of a nation's development, with implications for social equity and economic progress. This study aims to compare educational policies and practices in primary education across multiple countries, focusing on assessing access and equity. Engaging with magazines, articles, or books to gather research data constitutes the qualitative methodology employed in this study. The data collection approach adopted in this research involves utilizing the literature review method. Technical and source triangulation were implemented to ensure the data's validity. The data analysis technique follows the model proposed by Miles and Huberman, encompassing four stages: data collection, data reduction, data display, and drawing conclusions. The findings reveal significant variations in primary education policies and practices across countries. Successful strategies include targeted financial support for marginalized communities, teacher training programs, and curriculum adaptations that address local needs and cultures. This study underscores the importance of examining and learning from the experiences of different countries to improve access to quality primary education and promote equity. The identified successful strategies can inform policymakers, educators, and stakeholders in designing and implementing more effective policies to ensure all children have equal access to quality primary education. The study ultimately contributes to a broader understanding of the global pursuit of equitable and accessible primary education.